Combination verteporfin photodynamic therapy ranibizumab-dexamethasone in choroidal neovascularization due to age-related macular degeneration: results of a phase II randomized trial - Gallemore RP (Dove Medical Press, 2017)
Ron P Gallemore,1 Josh Wallsh,1 Henry L Hudson,2 Allen C Ho,3 Richard Chace,4 Joel Pearlman5 On behalf of the RADICAL Trial Group 1Retina Macula Institute, Torrance, CA, 2Retina Centers PC, Tucson, AZ, 3Wills Eye Institute, Philadelphia, PA, 4Eyesight Ophthalmic Services, Portsmouth, NH, 5Retinal Consultants Medical Group, Sacramento, CA, USA Purpose: To assess whether combination therapy (CT) reduces retreatments when compared to ranibizumab monotherapy (RM), while safely maintaining similar vision outcomes. Methods: In this 24-month trial, patients with age-related macular degeneration (AMD) were randomized to 1) quarter-fluence or 2) half-fluence triple therapy (verteporfin photodynamic therapy [vPDT] + ranibizumab + dexamethasone), 3) half-fluence double therapy (vPDT + ranibizumab), or 4) RM. The primary outcomes were number of retreatment visits and change from baseline in visual acuity (VA) at 12 months. Results: One hundred sixty-two subjects enrolled. There were 4.0 (P=0.02), 3.2 (P<0.001), 4.1 (P=0.03), and 5.7 retreatment visits through month 12, and 5.9 (P=0.03), 4.3 (P<0.001), 5.9 (P=0.02) and 8.7 through month 24, in groups 1, 2, 3, and 4, respectively (P-value comparing with RM). Month 12 VA score change from baseline (95% confidence interval) was +3.6 (–0.9 to +8.1), +6.8 (+2.4 to +11.1), +5.0 (+0.6 to +9.3), and +6.5 (+1.7 to +11.4), respectively. Conclusion: CT resulted in significantly fewer retreatment visits than a RM regimen at months 12 and 24. VA results appeared similar although wide confidence intervals preclude conclusions regarding vision outcomes. Keywords: age-related macular degeneration (AMD), combination therapy, ranibizumab, photodynamic therapy (PDT), verteporfin